A Comprehensive Literature Review of The Role Of Leptin In The Pathogenesis Of Systemic Lupus Erythematosus - Erick Persson Jeffry; Charles Sanjaya Seikka (International Medical Journal Corp. Ltd, 2025)
Background: The exploration of leptin's role in the pathogenesis of systemic lupus erythematosus (SLE) has garnered increasing attention in recent years, as evidenced by a series of studies that delve into the multifaceted relationships between this adipokine and autoimmune processes. Literature Review: Initial findings by (Francisco et al., 2018) suggest that leptin not only acts as an inflammatory marker but also plays a significant role in modulating immune responses, with leptin deficiency in mouse models protecting against autoantibody production and renal disease. (B. Taylor, 2021) expands on the pro-inflammatory effects of leptin, particularly its role in promoting Th1 and Th17 responses while diminishing Treg activity, a dysregulation observed in various autoimmune diseases, including SLE. The systematic review by highlights the complexity of leptin's role, indicating that it may function both as a pro-inflammatory and regulatory factor in SLE. This duality suggests that further research is needed to clarify the context-dependent effects of leptin on immune responses (). (M Kamel et al., 2023) contribute to this discussion by examining the association between serum leptin and disease activity in Egyptian SLE patients, reiterating the potential of leptin as a biomarker for disease progression, particularly in those with nephritis ((M Kamel et al., 2023)). Conclusion: In conclusion, the collected literature underscores the critical role of leptin in the pathogenesis of SLE, positioning it as both a biomarker and a potential therapeutic target. The evidence suggests that elevated leptin levels contribute to the dysregulation of immune responses characteristic of SLE, particularly through their impact on Treg populations and inflammatory pathways. However, the complexity of leptin's role necessitates further investigation to fully elucidate its mechanisms and implications for therapeutic interventions in SLE.